Returning CP-observables to the frames they belong - Ackerschott, Jona; Barman, Rahool Kumar; Gonçalves, Dorival; Heimel, Theo; Plehn, Tilman (SciPost physics, 2024)
Optimal kinematic observables are often defined in specific frames and then approximated at the reconstruction level. We show how multi-dimensional unfolding methods allow us to reconstruct these observables in their proper rest frame and in a probabilistically faithful way. We illustrate our approach with a measurement of a CP-phase in the top Yukawa coupling. Our method makes use of key advantages of generative unfolding, but as a constructed observable it fits into standard LHC analysis frameworks.